Microstructure of fatigue-tested F82H steel under multi-axial loadings - K. Fukumoto; T Onitsuka; T Itoh; H Sakasegawa; H Tanigawa (Nuclear Materials and Energy, 2018)
The fatigue process of multi-axial low cycle fatigue in F82H steels was investigated via multi-axial fatigue tests under non-proportional loading at 573 K in air. Various strain paths and strain waveforms were employed and the microstructure of each fatigue-tested F82H steel was examined. Sudden cyclic softening occurred at the initial stage of 50 cycles and the failure life associated with the circle loading test was significantly lower than those corresponding to push–pull and reversed torsion loading tests. Dislocation formation increased rapidly under all loading conditions. At failure, the dislocation density generated by circle loading at Δεeq = 1.0% was tens of times larger than those of the other loadings.Sudden cyclic softening results from the formation of mobile dislocations in grain interiors during the initial stage of loading. The significant reduction in the lifetime is directly correlated with the high density of dislocations generated during circle loadings. Keywords: Fatigue, F82H ferritic steel, Microstructure, Multi-axial loading